Time to Change Budgetary Priorities in the Eurozone - Paul De Grauwe; Yuemei Ji (Intereconomics, 2019)
With the spectre of a recession looming in the eurozone (and elsewhere), the policy question arises as to how much leeway do the fiscal authorities in the eurozone have to follow counter-cyclical fiscal policies aimed at providing some stimulus to the economy.
Keywords: 330